2004
DOI: 10.1074/jbc.m408659200
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Handoff of DNA from UvrA to UvrB Utilizing DNA-Protein Photoaffinity Labeling

Abstract: To better define the molecular architecture of nucleotide excision repair intermediates it is necessary to identify the specific domains of UvrA, UvrB, and UvrC that are in close proximity to DNA damage during the repair process. One key step of nucleotide excision repair that is poorly understood is the transfer of damaged DNA from UvrA to UvrB, prior to incision by UvrC. To study this transfer, we have utilized two types of arylazido-modified photoaffinity reagents that probe residues in the Uvr proteins tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 42 publications
(90 reference statements)
6
70
0
Order By: Relevance
“…Results of prior studies showed that the UvrABC system can carry out incision of a nicked strand, suggesting that UvrAB recognizes a nick as DNA damage. 20,30 Interestingly, we did not observe loading of UvrB onto nicked DNA using EMSA (data not shown). If UvrB dissociates from a nick during electrophoresis, we would not observe binding by UvrB to nicked DNA using EMSA.…”
Section: Evaluation Of Quantum Dot As a Molecular Pointer For Afm Imamentioning
confidence: 77%
See 2 more Smart Citations
“…Results of prior studies showed that the UvrABC system can carry out incision of a nicked strand, suggesting that UvrAB recognizes a nick as DNA damage. 20,30 Interestingly, we did not observe loading of UvrB onto nicked DNA using EMSA (data not shown). If UvrB dissociates from a nick during electrophoresis, we would not observe binding by UvrB to nicked DNA using EMSA.…”
Section: Evaluation Of Quantum Dot As a Molecular Pointer For Afm Imamentioning
confidence: 77%
“…Prior studies have shown that this fluorescein adduct can be recognized as a DNA lesion by the NER system. 20,29 A representative agarose gel and quantification of gels from three independent experiments are shown in parts B and C of Figure 3, respectively. In the agarose-EMSA assay, UvrB-DNA complexes ( Figure 3B, lane 3) were clearly resolved, indicating that UvrB was loaded onto damaged DNA by UvrA.…”
Section: Evaluation Of the Dna Binding Function Of Uvrb-qd Using Emsamentioning
confidence: 99%
See 1 more Smart Citation
“…These mutated amino acid residues, R367A, R289A/R367A, and E307A, are all located on domain 1b oppo- The black bar across the DNA strand indicates that the point of interaction between Phe 527 (F527), and the DNA is several bases downstream (more 3Ј) of the incision site. We have depicted, in various colors, the UvrB amino acid side chains that are thought to be important for DNA damage recognition and processing (5,6,14). A, UvrB has engaged the DNA adduct (red) using Tyr 95 and Tyr 96 (Y95/96).…”
Section: Discussionmentioning
confidence: 99%
“…7. UvrB is believed to first lock the non-damaged strand (14) into place by the interactions between the ␤-hairpin and domain 1b (see Fig. 1).…”
Section: Discussionmentioning
confidence: 99%